2021
DOI: 10.1002/aenm.202102660
|View full text |Cite
|
Sign up to set email alerts
|

Pyrrolidinium‐PEG Ionic Copolyester: Li‐Ion Accelerator in Polymer Network Solid‐State Electrolytes

Abstract: Nonflammable lithium‐ion batteries (LIBs) are developed by adapting polymer solid electrolytes, but their insufficient electrochemical performance has not been fully addressed to date. Crosslinked polymer gel electrolytes with minimal organic solvents (hard gels) are proven to be nonflammable electrolytes, but their lithium metal battery performance is not comparable to those of conventional liquid electrolyte‐based systems. Here, a semi‐interpenetrating polymer network (semi‐IPN) ion‐transporting solid film t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…[136] As shown in Figure 13F, the LiCoO 2 /P 1000 PEG-SPE/Li cell delivered a much higher initial discharge capacity than the cells with N-SPE and LiCoO 2 /P400, 2000, 4000PEG-SPE/Li, maintaining a consistent specific capacity at a high current rate (123 mAh g −1 at 2 C and 107 mAh g −1 at 3 C, respectively). [136] Finally, Yu et al reported a wide-temperature superior ionic conductive polymer electrolyte for Li-metal batteries. [55] The polymer electrolyte prepared by in situ polymerization of vinyl ethylene carbonate.…”
Section: Solid-state Polymer-based Electrolytementioning
confidence: 87%
See 1 more Smart Citation
“…[136] As shown in Figure 13F, the LiCoO 2 /P 1000 PEG-SPE/Li cell delivered a much higher initial discharge capacity than the cells with N-SPE and LiCoO 2 /P400, 2000, 4000PEG-SPE/Li, maintaining a consistent specific capacity at a high current rate (123 mAh g −1 at 2 C and 107 mAh g −1 at 3 C, respectively). [136] Finally, Yu et al reported a wide-temperature superior ionic conductive polymer electrolyte for Li-metal batteries. [55] The polymer electrolyte prepared by in situ polymerization of vinyl ethylene carbonate.…”
Section: Solid-state Polymer-based Electrolytementioning
confidence: 87%
“…Reproduced with permission. [136] Copyright 2021, Wiley-VCH. G) Li||NCM811 full cells with poly(vinyl ethylene carbonate) polymer electrolyte.…”
Section: Discussionmentioning
confidence: 99%
“…Establishing an insulating layer on Zn metal from coating methods, for example, a gelatin‐based coating, polyacrylonitrile (PAN) coating, and a hydrophilic interface can immobilize the H 2 O molecule and anion near anodes and deliver dense zinc flux. [ 20–22 ] Anti‐corrosion protected layer by chemical passivation methods can effectively suppress the side‐reaction of Zn and become independent of surface smoothness requirements from the coating methods. [ 23 ] But, due to the strong binding of solvent and insulating features, polymer coating and passivation layer usually bring increasing polarization and reduce kinetics performance.…”
Section: Introductionmentioning
confidence: 99%
“…However, their brittleness and poor contact with the electrodes make them difficult to adapt to the present lithium battery manufacturing processes . In contrast, solid-state polymer electrolytes (SPEs) such as poly­(ethylene oxide) (PEO), , poly­(ethylene glycol) (PEG), , polyacrylonitrile (PAN), poly­(propylene carbonate) (PPC), , and poly­(methyl methacrylate) (PMMA) , show better flexibility and interfacial compatibility with electrodes, making them easier to manufacture. However, low ionic conductivity at room temperature, low oxidation decomposition potential, and flammability limit the practical application of SPEs.…”
Section: Introductionmentioning
confidence: 99%